A deformation mechanism based material model for topology optimization of laminated composite plates and shells. (1st January 2017) - Luo, Quantian; Tong, Liyong
Abstract: This paper presents a novel deformation mechanism based material model for topology optimization of laminated plates and shells considering large displacements. Discussed firstly are the one-node hinges in optimum designs of plate and shell structures and the numerical issues caused by void elements in geometrical nonlinear analysis. To circumvent these two problems, we propose a new material model in which different penalties are applied to different strain energy terms related to extensional, shear, bending and extensional-bending coupling deformation mechanisms and void elements are removed in nonlinear finite element analysis. An efficient algorithm is developed by using the present material model and the moving iso-surface threshold method. Numerical results are presented for isotropic and composite plates and shells and compared with those available in the literature to validate the present material model.